Detection of circulating tumor cells in patients with pancreatic cancer by novel nano microfluidic chips and comprehensive nursing intervention: Circulating tumor cells in patients by novel nano microfluidic chips - Wang, Guiying; Luo, Lilin (Cellular and Molecular Biology, 2023)
It was to explore the detection efficiency of novel nano microfluidic chips on circulating tumor cells (CTCs) in pancreatic cancer (PC) patients and the effect of comprehensive nursing intervention on the life indicators of patients after PC surgery. PC, benign pancreas, and healthy volunteers were enrolled. The number and positive rate of CTCs in the subjects, the relationship between the number of CTCs in PC patients and clinical data, the recurrence rate, and the life indicators of patients after intervention were sorted out and analyzed. The positive rate of CTCs was 96.67% in PC group (29/30), 16.67% in benign pancreas group (5/30), and 0% in healthy controls. The positive CTCs in PC patients were correlated with vascular invasion (P<0.05). The recurrence rate after PC resection was 56.67% (17/30). The positive detection rate of nano microfluidic chip was 30/30 (100%), which was higher than against CellSeach 7/30 (23.33%), P<0.05. The physiological function score of intervention group (93.67±1.48) was higher as against controls (60.45±2.03), P<0.05. The social function score of intervention group (91.26±0.44) was higher as against controls (54.92±2.98), P<0.05. The novel nano microfluidic chip has high sensitivity and specificity for the detection of CTCs in PC patients. Postoperative comprehensive nursing intervention can improve the quality of life (QoL) and functional status of PC patients.